2013
DOI: 10.1186/1471-2393-13-73
|View full text |Cite
|
Sign up to set email alerts
|

A matched pair cluster randomized implementation trail to measure the effectiveness of an intervention package aiming to decrease perinatal mortality and increase institution-based obstetric care among indigenous women in Guatemala: study protocol

Abstract: BackgroundMaternal and perinatal mortality continue to be a high priority problem on the health agendas of less developed countries. Despite the progress made in the last decade to quantify the magnitude of maternal mortality, few interventions have been implemented with the intent to measure impact directly on maternal or perinatal deaths. The success of interventions implemented in less developed countries to reduce mortality has been questioned, in terms of the tendency to maintain a clinical perspective wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…Current evidence emphasises the impact of training on confidence, knowledge and skills of participants with minimal evidence for the clinical impact of training on maternal or perinatal morbidity or mortality. There are trials currently underway to look specifically at clinical outcomes from simulation‐based training . Further work is required in this area.…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence emphasises the impact of training on confidence, knowledge and skills of participants with minimal evidence for the clinical impact of training on maternal or perinatal morbidity or mortality. There are trials currently underway to look specifically at clinical outcomes from simulation‐based training . Further work is required in this area.…”
Section: Resultsmentioning
confidence: 99%
“…After promising results from a pilot project that built interest among local stakeholders, a prospective trial aim to implement and evaluate the impact of an intervention package at scale, was launched across the two rural districts of Huehuetenango and Alta Verapaz 17 . Given the nature of the intervention package, health centers and the municipalities were chosen as clusters and serve as the unit of delivery of the intervention and randomization to assess the impact of the intervention on the outcomes of all births occurring at the health center level.…”
Section: Methodsmentioning
confidence: 99%
“…Data were extracted from health center records by using an adapted 30‐question tool previously used in a pilot phase of the study 17 . Field workers were trained in data collection procedures including data protection and privacy.…”
Section: Methodsmentioning
confidence: 99%
“…Research on a remote Peruvian region comprised of mostly indigenous peoples found an association between biomass fuel use and increased risk of hypertension and higher blood pressure [9]. A current Guatemalan report seeks insight on indigenous perinatal mortality after construction of 68 centers for labor and delivery [39].…”
Section: Current Issuesmentioning
confidence: 99%